Pengetahuan Perawat Tentang National Early Warning System Score (NEWSS) dengan Pelaksanaannya di IGD & ICU Rumah Sakit - Sahensolar, Donny (Yayasan Syalom Cipta Sumikolah, 2025)
The National Early Warning Score (NEWS) is an early detection assessment system for detecting worsening patient conditions (Megawati et al., 2023). A nurse's knowledge of NEWSS can help coordinate nursing actions or care. Scoring skills can influence compliance with the scores obtained. The purpose of this study was to determine the relationship between nurses' knowledge of the National Early Warning System Score (NEWSS) and its implementation in the Emergency Room and Intensive Care Unit (ER) of Bhayangkara Hospital Level III. The type of research used in this study is descriptive analytic, examining the relationship between variables using a cross-sectional study. A cross-sectional approach is a research approach that uses a simultaneous approach or data collection at a single point in time. The population in this study was 24 nurses in the emergency department (ER) and 8 nurses in the intensive care unit (ICU). The total number of nurses was 32. The sample in this study was taken using a total sampling technique of 32 nurses. Based on the results of the study using the Chi Square test, the significant asymp value of P Value is 0.000 <0.05, The conclusion of this study is that there is a relationship between nurses' knowledge about the National Early Warning System Score (NEWSS) and its implementation in the Emergency Room and Intensive Care Unit (ER) of Bhayangkara Hospital Level III Manado. The suggestion from this study is that it is expected to increase knowledge, insight, and information for nurses, where nurses are an important part of the hospital who are required to provide good behavior in order to help patients achieve recovery.